Erythropoietin levels in the different clinical forms of hereditary spherocytosis - Rocha, Susana (2008)
Erythropoietin (EPO), the main growth factor responsible for the regulation of red blood cell production, may be overproduced when blood loss or haemolysis occurs. Patients with mild hereditary spherocytosis (HS) are able to maintain normal haemoglobin concentration, whereas typical and severe HS patients develop an anaemic state. Splenectomy usually reverses anaemia. We aimed to clarify the role of EPO in the response to enhanced spherocyte destruction, and to look for a linkage with the broad clinical spectra of HS. EPO levels, reticulocyte count and production index (RPI), other parameters used to classify HS and the protein deficiencies underlying HS were evaluated in previously diagnosed unsplenectomised (n ¼ 24) and splenectomised (n ¼ 10) patients presenting mild, typical or severe HS. A significant increase in EPO was observed in all unsplenectomised HS patients. In the mild form, a significant correlation of EPO with reticulocyte count and RPI was observed; however, this correlation disappeared in typical HS patients. Splenectomised HS patients presented a correction in EPO levels in all forms of HS, although the reticulocyte count and RPI sustained slightly higher values. Our data show HS as a disease linked to an overproduction of EPO, according to the severity of the disease; however, a disturbance in erythropoiesis seems to occur in typical HS. Moreover, splenectomy leads to a correction in the EPO levels.